Impact of Hearing Impairment on Marital Adjustment In Elderly Couples: Life Sciences-Psychology for curing mental health - Vivek Kumar Jha; Rajbir Singh (International Journal of Life Science and Pharma Research, 2022)
This present study was conducted to determine the relationship of marital adjustment with loss of hearing in elderly couples. To carry out the study, the subjects were audiologically tested and the marital adjustment questionnaire (MAQ) was administered along with hearing handicap inventory (HHI). The audiological assessment consisted of pure tonal audiometry (PTA), which was carried out in a sound treated room by air conduction (from 250 Hz to 8000 Hz) and the bone conduction (500 Hz to 4000 Hz). Hearing threshold was calculated by using the MAICO brand Audiometer (MA-42). The sample was 30 elderly couples without hearing aids. Among them, 15 couples having B/L severe hearing loss in male partner and female partner with normal hearing were placed in experimental group, while other 15 couples having no hearing loss placed in control group. Data analysis was carried out with the help of IBM-SPSS software. For statistical analysis, the Pearson correlation was used among pure tone average, marital adjustment and hearing handicap inventory. To see the difference in mean adjustment score of experimental and control group, t-test was applied. Pearson correlation showed negative significant correlation between HHI and Marital adjustment, between PTA and Marital adjustment. HHI and PTA revealed high positive correlation. The results show a strong connection between hearing loss in elderly couples and poor adjustment.